Ground load and float-ability analysis of trolley type landing gear - YANG Yu; ZHANG Ming; RUAN Shuang; SHI Xiazheng (Hangkong gongcheng jinzhan)
The compatibility of aircraft landing gear and pavement is of great significance to the ground motion ability of aircraft. In this paper, the landing gear load and tire load distribution under different working conditions for a large aircraft are calculated by using the Portland Cement Association method based on Westgard laminate theory and the United States Army Corps of Engineers method based on California bearing ratio（CBR）. The influence of the landing conditions, ground mobility, tire number, tire deflation and track widths on the aircraft classification number（ACN）is analyzed. The aircraft float-ability under rigid and flexible pavement is analyzed. Results show that the increased tire load and uneven load distribution caused by vertical overload and tire deflation can weaken the float-ability of aircraft to varying degrees, especially during turning and landing conditions with tail sinking, therefore, which need to be limited. Increasing the number of tires and the distance between them can improve the float-ability, but the structural design, strength margin and other factors should also be taken into consideration to optimize the design of trolley type landing gear.